A critical analysis of men's constructions of paying for sex: doing gender, doing race in the interview context - Huysamen, Monique (Department of Psychology, 2018)
Men from all walks of life pay for sex in various contexts every day, yet we know very little about the ways in which men make meaning of their paid sexual encounters, particularly in South Africa, where sex work is both illegal and highly stigmatised. South Africa's apartheid and colonial past, as well as contemporary concerns about HIV/AIDS, further complicates and impacts on the social meanings of sex work. This study explores the ways in which men make meaning of paying for sex, and how they negotiate their client identities in relation to their various intersecting social identities, such as their gender, sexuality, race, and class. Indepth interviews were conducted with 43 men who identified as clients of sex workers, through face-to-face, Skype video call or instant messenger interviews. This study is designed to contribute methodologically to knowledge on cross-gender interviews. It employs a critical and intersectional form of reflexivity to the analysis of its particular interview-participant dynamic, where a woman researcher interviewed men about their sexualities. I argue that men's motivations for participating in these interviews - such as gaining a sense of libidinal excitement or thrill, the desire to confess their engagement in a sexual taboo, the assumption that the interview encounter was transactional, to engage in a power struggle, and the desire to have their emotional needs met - also provided insights into both what motivates men to pay for sex and how they relate to sex workers. The study highlights the importance of employing an intersectional approach to understanding men's constructions of paying for sex. It argues that, in order to manage the stigma that is associated with paying for sex, men drew on dominant racist discourses, tropes stemming from the colonial era, about the black body as dirty and diseased and the white body as respectable and clean, to negotiate desirable client identities. Moreover, it argues that men valued the client-sex worker encounter as a "safe space" where sex workers, whom they constructed as their experienced teachers, would teach them the sexual skills that they (felt they) needed to better approximate idealised versions of masculinity outside of the paid encounter. However, for some men, paid sex was not only a place where dominant discourses of gender and sexuality were reproduced; it was also a safe space where they could secretly explore and experiment with their sexuality, highlighting how paid sexual encounters might offer opportunities for resisting and queering the strict boundaries of normative heterosexuality. Finally, based on the overall findings of this study, I put forward suggestions for legislative approaches to sex work that respond specifically to the South African context and address the stigma attached to sex work.